Cover, Volume 42, Issue 4. Issue 4 (15th April 2021) - Wang, Huijun; Xiao, Feifan; Dong, Xinran; Lu, Yulan; Cheng, Guoqiang; Wang, Laishuan; Lu, Wei; Yang, Lin; Chen, Liping; Kang, Wenqing; Li, Long; Pan, Xinnian; et al.
Abstract : The cover image is based on the Original Article Diagnostic and clinical utility of next‐generation sequencing in children born with multiple congenital anomalies in the China neonatal genomes project (CNGP) by Wenhao Zhou et al., https://doi.org/10.1002/humu.24170 .